The Effect of Quality of Work Life (QWL) on Job Satisfaction and Organization Citizenship Behavior (OCB) (A Study of Nurse at Numerous Hospitals In Malang, Indonesia) - Ruhana, Ika (FIA UB, 2019)
Good QWL is needed by the organization, in order to achieve organizational goals and increase satisfaction for employees, n this study is job satisfaction and OCB for nurses.The purpuse of the study is toÂ analyse and describe the influence of QWL on job satisfaction, the effect of QWL on OCB and the effect of job satisfaction on OCB. This research was conducted in four general hospitals that have type A, B, C and D. The samples in this study were nurses in the four hospitals. Based on the sampling technique obtained a sample of 175 respondents. The main instrument in collecting data by distributing questionnaires. The general hospital that is the location of this study is the Saiful Anwar Regional General Hospital (RSSA) located in Malang City with type A, Persada Hospital located in Malang city with Type B, Karsa Husada General Hospital (RSUKH) in Batu City with Type C and Madinah Islamic Hospital in Kasembon Malang Regency with Type D. The analysis technique used was descriptive analysis and inferential analysis with GSCA. The results of the descriptive analysis showed that nurses' QWL was perceived as neutral by nurses. Job satisfaction was perceived as agreed by nurses and OCB responded in agreement by the nurse. The results of hypothesis testing using GSCA shows that QWL has a positive and significant effect on job satisfaction, QWL has a positive and significant effect on OCB and job satisfaction has a positive and significant effect on OCB. Advice that can be given to the hospital is to further improve the QWL of nurses, especially those relating to compensation indicators because compensation is perceived as neutral by nurses, especially with the provision of fair and adequate compensation. the hospital must pay more attention to working conditions especially related to a healthy physical environment. Satisfaction with payroll is perceived as neutral by nurses, especially related to satisfaction with the salary and benefits provided by the hospital. Satisfaction with promotion also needs to be improved again, especially with regard to promotion opportunities and the provision of information about promotion opportunities. Nurse OCB was perceived as agreed by the nurse.Â Therefore OCB nurses are good, so they can be maintained or improved again.